Implementasi Augmented Reality Sebagai Media Promosi dan Visualisasi Bangunan Rumah - Prabowo, Husen; Kalifia, Anna Dina; Diwandari, Saucha (MEANS (Media Informasi Analisa dan Sistem), 2024)
Augmented reality in advertising and visualization of residential buildings to facilitate the provision of information and the presentation of information to consumers and potential consumers in residential areas for the bidding and presentation process, using fewer paper brochures and reducing the waste of paper and energy required to disseminate information there. This new technology will certainly increase the attractiveness and improve the efficiency of information transfer. This augmented reality application is a technology that allows objects or information to be displayed in 3D and viewed from a perspective that is very similar to the shape of the original object. The method used to create this application is (research and development). The steps include analyzing the potential and problems through preliminary research through desk study of field research, data collection through observation, and data collection through research